Effect of temperature on loss mechanism of 0.7PMN-0.3PZT ceramics - Siripong Somwan (2018)
© 2015 Elsevier B.V. In this work, 0.7Pb(Mg 1/3 Nb 2/3 )O 3 -0.3Pb(Zr 0.52 Ti 0.48 )O 3 (0.7PMN-0.3PZT) relaxor ferroelectric ceramic was prepared. The dielectric constant was measured by LCR meter at frequencies of 1-100 kHz to observe ferroelectric-paraelectric phase transition T m . To investigate effect of temperature on loss mechanism, 0.7PMN-0.3PZT ceramic was subjected to measurement electric field induced strain and polarization behavior at 0.2 Hz and 0.05 Hz by modified Michelson interferometric technique and Sawyer-Tower circuit with temperatures between 30 °C and 50 °C. The result showed dielectric constant peak at around 50 °C. The hysteresis of polarization and induced strain decreased to slimmer loop when temperature increased, where polarization hysteresis shows anti-clockwise direction when measured at 0.2 Hz but clockwise at 0.05 Hz of applied electric field frequency at subswitching field 6 kV/cm due to frequency dependence of electrical loss and caused accumulated depolarizing field inside material when lower spontaneous polarization appears to be temperature dependent. The change of linear polarization from positive to negative when the frequency was decreased contributed to a decrease of induced-strain and this is promising for application of actuators.